Overcoming Rooming-In Barriers: A Survey on Mothers' Perspectives - Consales, Alessandra; Crippa, Beatrice Letizia; Cerasani, Jacopo; Morniroli, Daniela; Damonte, Martina; Bettinelli, Maria Enrica; Consonni, Dario; Colombo, Lorenzo; Zanotta, Lidia; Bezze, Elena; Sannino, Patrizio; Mosca, Fabio; et al. (Frontiers in Pediatrics, 2020)
Background: The importance of rooming-in in promoting breastfeeding initiation and continuation within the Ten Steps for Successful Breastfeeding is widely acknowledged. However, adherence to this practice by healthcare facilities is lower than that of other Steps. A deeper knowledge of maternal rooming-in experience has been advocated to identify the most effective rooming-in policies, thus enabling mothers to have a positive experience when practicing it in the postpartum period. Aim: To investigate maternal knowledge of rooming-in and the most frequently encountered barriers and possible facilitators of adherence to the practice, according to their experience. Study design and methods: We enrolled mothers who delivered healthy term or late preterm infants during the month of January 2019 in a tertiary referral centre for neonatal care in Milan, Italy. At discharge, a structured interview about mothers’ rooming-in experience was administered by healthcare professionals. Basic subjects’ characteristics and mode of feeding were recorded. Results: The enrolled population included 328 mothers and 333 neonates. The great majority of mothers knew of rooming-in and 48.2% practiced it continuously. The 86.3% of mothers was aware of the beneficial effects of rooming-in; promotion of mother-infant bonding, increased confidence in taking care of the baby and ability to recognize baby’s feeding cues were the most frequently cited, whereas improving breastfeeding was reported by a limited number of mothers, unless they were asked a specific question about it. The main reported obstacles were fatigue (40.5%) and caesarean section related difficulties (15.5%); night was the most critical time of the day for rooming-in. Strategies suggested by mothers for improving rooming-in were increased assistance to the dyad, organizational and structural changes and the possibility to have a family member during the night. Additionally, mothers who adhered to rooming-in practice continuously during hospital stay had a higher exclusive breastfeeding rate at discharge compared to mothers who did not. Conclusions: Our study contributes to a deeper knowledge of maternal rooming-in experience in an Italian tertiary maternity. We underline the importance of providing a tailored support to the mother-infant dyad in order to overcome rooming-in barriers perceived by mothers and promote a positive rooming-in experience.